Influence of the link between resources and behavioural factors on the entrepreneurial intentions of electrical installation and maintenance work students - Ifeanyi Benedict Ohanu; Taiwo Olabanji Shodipe (Journal of Innovation and Entrepreneurship, 2021)
With a theory of planned behaviour (TPB) framework, this study examined how the link between resources and behavioural factors influence the entrepreneurial intentions of electrical installation and maintenance work (EIMW) students. It showed how available resources, which are defined as those controlled by the technical institutions but are accessible by the students, influence their behaviour and consequently their entrepreneurial intention. Different approaches are used in the study to analyse the primary data collected from EIMW students and an empirical analysis was done using structural equation model. The study showed the robustness of TPB model in the face of available resource that attitude, subjective norms and perceived behavioural control are behavioural factors that can be positively influence by several exogenous factors to enhance EIMW students' entrepreneurial intentions. The results of the study enhance the institutional training of staff and instructors at all management to give career counselling services and be vast in the career opportunities available in the field of study. This skill will motivate EIMW students towards establishing their business venture.
Keywords: 650; Behavioural factors; EIMW; Entrepreneurial intentions; Institutional resources